The Effect of Attitudes and Habits in Online Mathematics Learning on Cognitive Learning Outcomes of Senior High School Students - Herawati, Herawati; Susanta, Agus; Zamzaili, Zamzaili (Jurnal Pendidikan MIPA, 2023)
This study aims to determine the effect of attitudes and habits of learning mathematics through online learning on students' cognitive learning outcomes. This type of research is correlation research using ex post facto design. The research population was all class X IPA students at senior high school 7 Bengkulu City for the 2020/2021 academic year with 320 students. The research sample of 107 students from three classes was selected by a simple random sampling technique where the distribution of students' abilities in each category was not different. The study results show that attitudes toward learning mathematics in online learning have a direct positive effect on students' cognitive learning outcomes. The habit of learning mathematics in online learning has a direct and positive effect on students' cognitive learning outcomes. Suggestions from this study in improving student learning outcomes teachers need to develop student attitudes and learning habitsKeywords: mathematics attitudes, study habits, learning outcomes, online learning.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp203-212